Activity and distribution of intracellular carbonic anhydrase II and their effects on the transport activity of anion exchanger AE1/SLC4A1. (24th September 2013) - Al‐Samir, Samer; Papadopoulos, Symeon; Scheibe, Renate J.; Meißner, Joachim D.; Cartron, Jean‐Pierre; Sly, William S.; Alper, Seth L.; Gros, Gerolf; Endeward, Volker
Key points Controversial results have been reported on the hypothesis that the cytosolic carbonic anhydrase II (CAII) of the red cell is largely bound to the cell's Cl−/HCO3− exchanger AE1, forming a 'metabolon complex' that greatly enhances transport activity of AE1. In examining so far untested aspects of this hypothesis, we report that fluorophore‐labelled AE1 and CAII proteins, expressed in tsA201 cells, neither colocalize at the cell membrane nor show close proximity by Förster resonance emission spectroscopy. Antibody against Flag‐tagged AE1 expressed in tsA201 cells co‐immunoprecipitates coexpressed ankyrin but not CAII. CAII‐deficient human red blood cells with substantial CAI activity exhibit HCO3− permeabilities identical to those of normal red cells. A mathematical model of CO2/HCO3− transport of red cells indicates that this process occurs more rapidly when the CA of the cell is distributed homogeneously across the cytoplasm rather than being bound to the membrane interior. Abstract We have investigated the previously published 'metabolon hypothesis' postulating that a close association of the anion exchanger 1 (AE1) and cytosolic carbonic anhydrase II (CAII) exists that greatly increases the transport activity of AE1. We study whether there is a physical association of and direct functional interaction between CAII and AE1 in the native human red cell and in tsA201 cells coexpressing heterologous fluorescent fusion proteins CAII‐CyPet and YPet‐AE1. In these doubly transfected tsA201 cells, YPet‐AE1 is clearly associated with the cell membrane, whereas CAII‐CyPet is homogeneously distributed throughout the cell in a cytoplasmic pattern. Förster resonance energy transfer measurements fail to detect close proximity of YPet‐AE1 and CAII‐CyPet. The absence of an association of AE1 and CAII is supported by immunoprecipitation experiments using Flag‐antibody against Flag‐tagged AE1 expressed in tsA201 cells, which does not co‐precipitate native CAII but co‐precipitates coexpressed ankyrin. Both the CAII and the AE1 fusion proteins are fully functional in tsA201 cells as judged by CA activity and by cellular HCO3− permeability (<inline-graphic xlink:href="ark:/27927/pgg4t6km01t" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />) sensitive to inhibition by 4, 4′‐Diisothiocyano‐2, 2′‐stilbenedisulfonic acid. Expression of the non‐catalytic CAII mutant V143Y leads to a drastic reduction of endogenous CAII and to a corresponding reduction of total intracellular CA activity. Overexpression of an N‐terminally truncated CAII lacking the proposed site of interaction with the C‐terminal cytoplasmic tail of AE1 substantially increases intracellular CA activity, as does overexpression of wild‐type CAII. These variously co‐transfected tsA201 cells exhibit a positive correlation between cellular <inline-graphic xlink:href="ark:/27927/pgg4t6km051" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> and intracellular CA activity. The relationship reflects that expected from changes in cytoplasmic CA activity improving substrate supply to or removal from AE1, without requirement for a CAII–AE1 metabolon involving physical interaction. A functional contribution of the hypothesized CAII–AE1 metabolon to erythroid AE1‐mediated HCO3− transport was further tested in normal red cells and red cells from CAII‐deficient patients that retain substantial CA activity associated with the erythroid CAI protein lacking the proposed AE1‐binding sequence. Erythroid <inline-graphic xlink:href="ark:/27927/pgg4t6km140" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> was indistinguishable in these two cell types, providing no support for the proposed functional importance of the physical interaction of CAII and AE1. A theoretical model predicts that homogeneous cytoplasmic distribution of CAII is more favourable for cellular transport of HCO3− and CO2 than is association of CAII with the cytoplasmic surface of the plasma membrane. This is due to the fact that the relatively slow intracellular transport of H+ makes it most efficient to place the CA in the vicinity of the haemoglobin molecules, which are homogeneously distributed over the cytoplasm.